GAMMA RAY AND EMS INDUCED POLYGENIC VARIABILITY IN M2 AND M3 POPULATIONS OF AROMATIC RICE - AND S . K. CHAKRAVARTI , SANJEEV SINGH, RISHI KUMAR SHARMA (The Bioscan, 2018)
In the present study, most of the quantitative traits were studied to screen out the useful and desirable mutants in the mutagen treated population. A sharp decline in grain yield per plant might be attributed to decrease in mean performance of these quantitative traits affecting induced polygenic variability. The present investigation clearly demonstrated the high potentials of 50kR gamma rays +0.2% EMS followed by 0.5% EMS and 50kR gamma rays in inducing variability for yield and component traits in most of the characters in both the genotypes as well as generations. Traits like plant height, days to 50% flowering, days to maturity, panicle length, number of grains per panicle, number of panicle bearing tillers per plant, 100-seed weight and grain yield per plant showed positive and negative shifts in mean in both the varieties of aromatic rice in both generations. These traits, as expected because of their positive correlation with grain yield, contributed significantly towards grain yield.